Constitutive models for rubber XI : proceedings of the 11th European conference on constitutive models for rubber, Nantes, France, 25-27 June 2019 /: proceedings of the 11th European conference on constitutive models for rubber, Nantes, France, 25-27 June 2019. (2019) - Unknown
No abstract available